The Identification of Kutai Kartanegara Traditional Architecture Identity Based on Comparative Analysis - Arif Budi Sholihah; March Endika (Journal of Architectural Research and Design Studies, 2017)
Kutai Kartanegara in the past was part of The Kingdom of Kutai, the oldest kingdom in Indonesia from the 4th to to 13th century. However, the data about this kingdom is very limited including the information about the architecture at that era. The interest to identify the character of Kutai Kartanegara such as the architecture has grown from the government and the society as the media to express the local identity. Thus, this research aims to identify the traditional architectural features of Kutai Kartanegara based on comparative analysis with the house of Lamin Dayak Kenyah and Architecture of Melayu Perak Malaysia. The method used in this research is comparison between traditional architecture of Dayak ethnicity and Malay traditional architecture through literature review. The result of library studies is then compared with the empirical data about traditional architecture of Kutai Kartanegara from field observation and measured drawing to one of the selected cases of traditional house of Kutai. From the findings of this research, it can be concluded that besides there is similarity with the two comparing architectures, the traditional architecture of Kutai has the specialty from the morphological aspect of layout and orientation. In addition, it also functions as single family dwelling with simpler geometrical ornamentation.Key Word: traditional architecture, identity, Kutai Kartanegara.